How Did Mathematics Postgraduates Obtain Tacit Knowledge of Mathematical Problem Solving? - Yang, Zezhong; Wang, Tong; Zhu, Ming; Qu, Zhaohua (American Journal of Education and Learning, 2017)
This research focused on the obtainment of mathematics postgraduates’ tacit knowledge of Mathematics problem solving, investigated 172 mathematics postgraduates with a closed-ended structured questionnaire which was formed based on the early interview. The results indicated that mathematics postgraduates’ tacit knowledge of Mathematics problem solving mainly came from their teachers’ explanation and demonstration about mathematics problem solving, their practice of mathematics problem solving, and their learning to knowledge of mathematics problem solving from related book. The other factors of teaching and learning impacted on the obtainment of tacit knowledge, but their contribution rate was not large. So we suggest that the college mathematics teachers should teach mathematics problem solving with Apprentice style and pay attention to guiding students to learn knowledge about mathematics problem solving.